Poezja w podroży i translatorskie synopsis. Komentarz do Bibliografii przekładów literatury chorwackiej w Polsce w 2018 roku - Majdzik Papić, Katarzyna (Przekłady Literatur Słowiańskich, 2020)
This article summarizes and discusses the body of translations from Croatian literature published in Poland in 2018. The most significant offering to appear on the Polish market that year was a multilingual collection of mid-career poetry by Dorta Jagić entitled The Portrait of The Body, containing Croatian originals and their translations into Polish (by M. Wierzbicka) and English (by D. Šodan, M. Đurđević). “Synoptic” editions (bilingual or multilingual) allow the reader to view both the original and its translation, which has three major benefits: it contributes to a better circulation of texts; enables deziluzionist reading (the awareness of the difference between the original and the translation); and establishes an intertextual bond between the collected texts.